The Relevance Of Ethical Principles On The Quality Of Nigerian Tertiary Education - Kani, Umar Mohammed (2020)
The central purpose of this study is investigating the problem of quality in Nigerian tertiary education within the context of ethics, guided by pragmatism and utilitarianism, to theorise associated factors and offer suggestions from ethical perspectives for improvement. It followed from the perception of stakeholders and general public that quality of Nigeria’s tertiary education has declined and the problem has not been holistically researched from the ethical viewpoint. Being a philosophical study through empirical approach, philosophical and qualitative methods were employed. Philosophical inquiry was applied for comprehensive view of key concepts of the topic and theories that underpinned the study while qualitative method was used for data collection and analysis. Aspects of the philosophical method were applied again in discussion of the findings. Semi-structured interviews were administered to 22 purposively selected participants from 11 governmental agencies and institutions that represent Nigeria’s tertiary education system. In addition, document analysis supplemented the in-depth interviews as instruments for data collection. The data was analysed using a combination of thematic analysis framework of Braun and Clarke, positivism of Silverman and interpretivism of Miles and Huberman, in which categorised themes constituted by subthemes were derived using synthesis of the three models. Findings revealed that gap between document provisions and practice, conflict, and deformalisation are topical issues of ethical concern in the system which caused preventable difficulties in the modus operandi